2011
DOI: 10.5367/te.2011.0068
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Tourist Spending in Cross-Sectional Studies and at Danish Destinations

Abstract: This article begins with a meta-analysis style review of the determinants of tourist spending according to more than 50 cross-sectional studies published in academic journal articles during the period 1995–2009. The studies are grouped using factor analysis based on the determinants included or not included in each study. Following the structured review, a conceptual model of the determinants of tourist spending is proposed. In the empirical part of the study, which is based on a survey with more than 11,000 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
3
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 69 publications
7
91
3
11
Order By: Relevance
“…Furthermore, researchers can use four different ways to measure visitors' spending (per person per night, per person per stay, per travel party per night and per travel party per stay) in order to provide extra utility for the users, as suggested by Kozak et al (2008) and Marcussen (2011 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, researchers can use four different ways to measure visitors' spending (per person per night, per person per stay, per travel party per night and per travel party per stay) in order to provide extra utility for the users, as suggested by Kozak et al (2008) and Marcussen (2011 …”
Section: Resultsmentioning
confidence: 99%
“…Additional to the meta-analysis of 55 cross-sectional studies conducted by Marcussen (2011), our study also tested the influence of further variables such as the purpose of visiting a specific cultural event and the perception of authenticity of the CM. This paper reveals that motives of the visit to the event influence the estimated expenditure; in particular, the motivation to visit the event in order to experience something different produces an increase in expenditure both on accommodation and on food and beverages.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Second, the paper provides empirical estimates on the elasticity of expenditures with respect to length of stay and travel party size, which are two factors that the literature has seen as important for marketing purposes (Marcussen, 2011). Third, the analysis includes several factors that are less commonly explored in tourism expenditure analysis (Brida & Scuderi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2004) stated that service quality and satisfaction have been critical concepts in the fields of recreation and tourism, as well as in marketing, because they may be used as indicators of profitability and the successful achievement of organizational objectives. In addition, many researchers have found that a high level of satisfaction leads to greater customer loyalty to certain services and/or products (Bernini and Cagnone, 2012;Marcussen, 2011;Naidoo et al, 2010;Yoon and Uysal, 2005) and that consumer satisfaction, by increasing loyalty, helps to secure future income (Anderson et al, 1997). Furthermore, in recent years satisfaction has begun to be used in studies that aim to explain tourism expenditure (Cárdenas-García et al, 2016).…”
Section: Literature Review -Tourist Satisfactionmentioning
confidence: 99%